Lâmina e frequência de irrigação, substrato e adubação na aclimatização de mudas micropropagadas de antúrio (Anthurium maricense) - Campos, Arlene Santisteban (2017)
Anthurium maricense is a species with great potential for commercialization, however, for a commercial scale production, seedlings must be produced by micropropagation, a tissue culture technique that has five important stages. The last one, the acclimatization, is one of the most critical, often leading to high mortality rates, low rates of development and high lack of uniformity of plantlets, mainly due to the lack of information at this stage. To fill this gap with relevant information on the adequate management of seedlings during this stage, the present work had the objective of evaluating the effect of different frequencies and irrigation depths, as well as of different substrates and fertilizer doses in the acclimatization of micropropagated plantlets of A. maricense. The research was divided in four experiments, carried out in a screen (80%) belonging to Embrapa Tropical Agroindustry, located in the Fortaleza, Ceará, Brazil. During the experiments the air temperature and humidity were registered every 10 minutes. Physico-hydric and physico-chemical analyzes were performed on samples of the substrates. The design was a completely randomized, composed of five treatments, four replicates and four plantlets per plot, individually grown in 415 mL pots. In experiment I, treatments consisted of five irrigation depths: 50%; 75%; 100%; 125% and 150% of water retention capacity (WRC) in the substrate. In experiment II, treatments consisted of five irrigation frequencies: 0.5; 1; 2; 3 and 4 irrigations per day. In experimente III, five substrates were tested: HS Flores; and coconut fiber plus earthworm compost in proportions of 0.5:1.0; 1:1; 2:1 and 3:1. In experiment IV, five doses of slow-release fertilizer (Osmocote® 15:9:12): 0.0; 2.5; 5.0; 7.5 and 10.0 kg m-3. In experiments I, II and IV the plantlets were grown on the commercial substrate HS Flores. In experiments I, III and IV, the frequency of irrigation was twice a day. The irrigation depth for experiments II, III and IV was equivalent to 100% of WRC. On alternate days the plantlets of experiments I, II and III received leaf fertilization. The variables analyzed were: leaf height variation (LHV), number of leaves variation (NLV), largest leaf area variation (LLAV), pot occupation (PO), net photosynthetic rate (A), internal carbon (Ci), leaf temperature (Ti) and leaf moisture (Ui). The results showed the best development of the A. maricense micropropagated plantlets when: irrigated with depths of the 150% of WRC; submitted to the frequency of four daily irrigations; cultivated on the substrate composed of coconut fiber and earthworm compost in the proportion of 3:1; and Osmocote® fertilizer dose of 6.40 kg m-3, throughout the experiment.